ANALISIS SIFAT MELAWAN HUKUM FORMIL TERHADAP PELAKU TINDAK PIDANA KORUPSI BERDASARKAN PASAL 2 DAN PASAL 3 UNDANG-UNDANG NOMOR 20 TAHUN 2001 - M DANI FARIZ AMRULLAH; Yuli Kasmarani; Dora Mustika (Universitas Islam Negeri Raden Fatah Palembang, 2024)
Corruption is an urgent problem that must be addressed immediately in order to achieve healthy economic growth. Various records show an increase and development of corruption models that occur. The legal enforcement mechanism for criminal acts of corruption is something that must be paid attention to because it ensures its implementation is correct, fair, there is no arbitrariness and no abuse of power. The focus of discussion in this research is the concept of the nature of being against formal law in criminal acts of corruption in Indonesia, and the existence of the nature of being against formal law in criminal acts of corruption at this time. This research uses a normative juridical approach, namely by analyzing library materials or secondary data consisting of legal texts, court decisions, official documents and other legal literature. This research concludes that the concept of the nature of being against formal law in articles 2 and 3 of Law Number 20 of 2001 concerning criminal acts of corruption in Indonesia is if the act violates social norms, norms of decency or ethics, moral norms and has violated propriety. prudence and necessity adhered to in person-to-person relationships in society. After the Constitutional Court decision Number: 25/PPU-XIV/2016, formal offenses were changed to material offenses. The deletion of the word